Acetyl-11-Keto-β-Boswellic Acid (AKBA) Prevents Lipopolysaccharide-Induced Inflammation and Cytotoxicity on H9C2 Cells. (30th March 2022) - Taherzadeh, Danial; Baradaran Rahimi, Vafa; Amiri, Hamed; Ehtiati, Sajjad; Yahyazadeh, Roghayeh; Hashemy, Seyed Isaac; Askari, Vahid Reza
Abstract : Acetyl-11-keto-beta-boswellic acid (AKBA), the major component of Boswellia serrata, exhibits anti-inflammatory activities. This in vitro study investigated the protective effects of AKBA against lipopolysaccharide (LPS)-induced cardiac dysfunction. In this study, the H9C2 cardiomyocytes were pretreated with AKBA (2.5, 5, and 10 μ M for 24 h), and then cotreated with LPS for another 24 h. The MTT assay, ELISA test kits, and quantitative real-time PCR analysis assessed the cell viability, levels of proinflammatory factors (IL- β, IL-6, TNF- α, and PGE2), and the gene expression of IL- β, IL-6, TNF- α, iNOS, and COX-2, respectively. The nitric oxide (NO) and thiol levels were also measured using a biochemical assay. The results indicated that LPS exposure markedly reduced cell viability and total thiol content, but increased the inflammatory cytokines, NO metabolites, and gene expression of proinflammatory mediators in H9C2 cells. AKBA pretreatment significantly altered the mentioned factors induced by LPS. Our results demonstrated that AKBA might be a promising therapeutic agent for treating sepsis-related cardiac dysfunction in the future.